Americans' Use of Time, 1985 - Robinson, John ([Verlag nicht ermittelbar], 1993)
For this data collection, respondents were asked to record in single-day time diaries each activity they engaged in over a 24-hour period. The time diary data were gathered through three different data collection methods: mail-back, telephone, and personal interviews. Respondents were instructed to describe in the diaries when the activity began, the time the activity ended, where it occurred, and who was present when the activity took place. Demographic variables include household type, respondent's sex, marital status, age, educational level, occupation, and work hours, number of children in the household under 5 and 18 years of age, and household income. Other variables focus on total work time, total time for meals at work, total minutes at work engaged in nonwork activities, total work break in minutes, and total time traveling to and from work. Data are also provided on total time spent on meal preparation and cleanup, housecleaning, outdoor chores, laundry, ironing, clothes care, home repair, baby care, child care, shopping for food, and traveling to and from food shopping. Respondents also reported total time spent on personal care, medical care, family financial activities, and sleeping, as well as time spent attending school, classes, seminars, special interest group meetings, religious meetings, sports events, and other social activities.